Development and wear resistivity performance of SiC and TiB2 particles reinforced novel aluminium matrix composites - Abhijit Bhowmik; Binayak Sen; N. Beemkumar; Jasgurpreet Singh Chohan; Pardeep Singh Bains; Gurpartap Singh; Ambati Vijay Kumar; Johnson Santhosh A (Results in Engineering)
The aerospace and automotive industries, in particular, rely heavily on aluminium matrix composites because of their exceptional strength-to-mass ratio and resistance to high temperatures. This study investigates the development and wear resistivity performance of Aluminium Matrix Composites (AMCs) reinforced with SiC and TiB2 particles. The experimental work involved fabricating AMCs using Aluminium Alloy 7075 as the matrix material with varying weight percentages of SiC and TiB2 reinforcements. Tribological tests were conducted under different conditions of applied load, sliding speed, and sliding distance to analyze the wear behavior of the composites. Results revealed that higher weight percentages of reinforcement led to lower wear rates, particularly at elevated sliding speeds. X-ray diffraction analysis confirmed the presence of SiC and TiB2 particles in the composites. It is observed that greater applied loads caused greater wear rates, bigger grooves, and substantial frictional heat production, demonstrating a direct relationship between load weight and wear performance. The study indicated that sticky wear management lowered wear rates at longer sliding distances not abrasive wear at shorter distances. The significance of this study lies in its contribution to optimizing the composition of multi-phase reinforced AMCs for enhanced wear resistance in various industrial applications.